Phenotypic and cell wall proteomic characterization of a DDR48 mutant candida albicans strain - El Khoury, Pamela (2019)
Candida albicans is an opportunistic fungus possessing multiple virulence factors controlling pathogenicity. Cell wall proteins are the most important among these factors, being the first elements contacting the host. Ddr48 is a cell wall protein consisting of 212 amino acids. A DDR48 haploinsufficient mutant strain was previously found necessary for proper oxidative stress response and drug resistance. In this study, we aimed to further elucidate the role of Ddr48 by performing additional phenotypic characterization assays. A combinatory proteomic and bioinformatics approach was also undertaken to determine differentially expressed cell wall proteins. Results showed that the mutant strain exhibited a 10% decrease in adhesion mirrored by a 20% decrease in biofilm formation, and slight sensitivity to menadione, diamide, and SDS. Both strains showed similar hyphae formation, virulence, temperature tolerance, and calcofluor white and Congo red sensitivities. Furthermore, a total of 8 and 10 proteins were identified exclusively in the wild-type strain grown under filamentous and nonfilamentous conditions respectively. Results included proteins responsible for superoxide stress resistance (Sod4 and Sod6), adhesion (Als3, Hyr4, Pmt1, and Utr2), biofilm formation (Hsp90, Ece1, Rim9, Ipp1, and Pra1) and cell wall integrity (Utr2 and Pga4). The lack of detection of these proteins in the mutant strain correlates with the observed phenotypes.